MODERN TECHNOLOGY APPLICATIONS IN THE PROTECTION OF SILK ROAD CULTURAL RELICS - Fan Yu Jian, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: The Silk Road was one of the most important trade and cultural exchange routes in human history, connecting Asia, Europe, and Africa. Along this route, numerous cultural relics, ancient cities, manuscripts, temples, mosques, murals, and archaeological sites were created, reflecting the diversity of civilizations and intercultural communication. However, due to natural aging, environmental changes, urbanization, tourism pressure, and armed conflicts, many Silk Road cultural relics face serious threats. In recent years, modern technologies such as digital imaging, 3D scanning, artificial intelligence, remote sensing, virtual reality, and environmental monitoring have been increasingly applied in the field of cultural heritage protection. These technologies have greatly improved the efficiency and scientific level of relic conservation. This paper analyzes the significance of Silk Road cultural heritage, discusses the major threats to its preservation, examines the application of modern technologies in relic protection, and explores future development trends. The study aims to provide theoretical references for sustainable cultural heritage conservation along the Silk Road.